Principles of engineering organization - Wearne, S. H. (Engineering management., 1993)
Helps engineers and managers in understanding and improving systems of organization. This book provides a review of principles and some analysis of examples drawn from a range of engineering activities. Alternatives are reviewed and their potential advantages and disadvantages are also compared.